2017
DOI: 10.1371/journal.pone.0180598
|View full text |Cite
|
Sign up to set email alerts
|

Convergence between parent report and direct assessment of language and attention in culturally and linguistically diverse children

Abstract: Parent report is commonly used to assess language and attention in children for research and clinical purposes. It is therefore important to understand the convergent validity of parent-report tools in comparison to direct assessments of language and attention. In particular, cultural and linguistic background may influence this convergence. In this study a group of six- to eight-year old children (N = 110) completed direct assessments of language and attention and their parents reported on the same areas. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…One important aim of this study was to quantify the association between LD trajectories across preschool years and later literacy skills using parent report measures in a population sample. Parent report has been proved to be a practical and effective means of obtaining information about child development (Ebert, 2017;Feldman et al, 2005;Libertus et al, 2015;Sachse & Von Suchodoletz, 2008) and is commonly used for assessment of children's language and literacy for research and screening purposes. Clearly, the literature on the relationship between oral language and literacy will benefit from consideration of the language and literacy skills derived from parent reports.…”
mentioning
confidence: 99%
“…One important aim of this study was to quantify the association between LD trajectories across preschool years and later literacy skills using parent report measures in a population sample. Parent report has been proved to be a practical and effective means of obtaining information about child development (Ebert, 2017;Feldman et al, 2005;Libertus et al, 2015;Sachse & Von Suchodoletz, 2008) and is commonly used for assessment of children's language and literacy for research and screening purposes. Clearly, the literature on the relationship between oral language and literacy will benefit from consideration of the language and literacy skills derived from parent reports.…”
mentioning
confidence: 99%
“…Thus, it is possible that caregivers may misjudge the language skills of children. Even so, research has suggested that such reports are generally consistent with direct assessment [ 65 , 66 ] and that both are similarly predictive of language delay at age 3 [ 67 ]. Nevertheless, it would be useful for future research to replicate the present findings using direct, individual language assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Once Part I was complete, they were given instructions to prepare for Part II. They were provided a list of pronouns and pronominal determiners and were asked to carefully observe their child's use of those words during the following 24-48 h. This feature of our report-the period during which caregivers were asked to directly observe an aspect of their child's behavior-makes our report a hybrid between a caregiver diary (a classic tool in language acquisition research, e.g., Clark, 1995;Dromi, 1987;Tomasello, 1992) and a caregiver questionnaire (e.g., the MacArthur-Bates Communicative Development Inventory; Fenson et al, 1993). The instructions explained that caregivers would be required to answer questions about their child's use of these words in the second report (Part II) (we did not specifically mention our interest in form vs. meaning, nor do we expect most caregivers to be aware of this distinction).…”
Section: Methodsmentioning
confidence: 99%